A 3D Camera User Interface for Wrist Angle Monitoring in Piano Performances - MacRitchie, Jennifer; Baylis, Christopher (Les Cahiers de la Société québécoise de recherche en musique, 2016)
Injuries are common over a performing musician’s career and wrist injuries are the most frequent site of pain for pianists. Although general recommendations insist on keeping wrists in a “neutral” position to avoid injury, this is rarely done in practice. Recent advances in motion capture technology may aid in raising students’ awareness of the propensity to use wrist positions outside of the recommended “neutral.” These technologies may be used to measure precise wrist positions in piano playing in order to set specific thresholds for avoiding injury. This paper discusses various advantages and limitations of motion capture technologies, including data visualization and usage within the music instrument pedagogy framework in order to define a set of requirements for an accessible motion-tracking system. A prototype of a dedicated image-processing-based system with a graphical user interface that meets these requirements is described. This system uses passive coloured markers and a standard 3D camera, encouraging use outside the traditional laboratory environment. Simple camera calibration options and basic hand tracking from aerial view images allow monitoring of wrist flexion/extension over short video recordings. Measurements are compared to flexion/extension thresholds recommended for typists to prevent carpal tunnel pressure, and moments of approaching or exceeding these thresholds are flagged to the user both in real time and in post-performance. Potential applications include monitoring the practice of short technical passages without restriction of instrument or location.